Influence of Energy Intake and Nutritional Status on Work Productivity Among Construction Workers: A Case Study of the Merdeka Square Revitalization Project, Medan - Mila Zahara; Rani Suraya; Nadya Ulfa Tanjung (The Indonesian Institute of Science and Technology Research, 2025)
Workers involved in revitalization projects are vulnerable to reduced productivity due to physically demanding tasks, time constraints, and challenging environmental conditions such as heat, noise, and long hours. These factors can lead to fatigue, stress, metabolic disorders, and poor nutritional intake, which in turn reduce endurance and focus. This study examines the influence of energy intake and nutritional status on work productivity among workers at the Merdeka Square Revitalization Project in Medan City. A quantitative cross-sectional design was used, involving 77 respondents. Data were analyzed using univariate, bivariate, and multivariate logistic regression tests. After controlling for confounders, both energy intake and nutritional status significantly affected work productivity (p < 0.05). Although excess energy intake was not statistically significant (Exp(B) = 1.319; 95% CI: 0.375–4.642), it still posed a 1.3 times greater risk of reduced productivity compared to adequate intake. In contrast, insufficient energy intake was significant (p = 0.030; Exp(B) = 5.375), with a 5.4 times greater risk of lower productivity. Nutritional status, both overnutrition (p = 0.009; Exp(B) = 10.039) and undernutrition (p = 0.002; Exp(B) = 14.898), significantly affected productivity. The Nagelkerke R² value of 0.354 indicates that these variables explain 35.4% of the variance in work productivity.